Between biblical criticism and poetic rewriting : interpretative struggles over Genesis 32:22-32 - Tongue, Samuel. (Biblical Interpretation Series, 2014)
In Between Biblical Criticism and Poetic Rewriting , Samuel Tongue offers an account of the aesthetic and critical tensions inherent in the development of the Higher Criticism of the Bible. Different 'types' of Bible are created through the intellectual and literary pressures of Enlightenment and Romanticism and, as Tongue suggests, it is this legacy that continues to orientate the approaches deemed legitimate in biblical scholarship. Using a number of ancient and contemporary critical and poetic rewritings of Jacob's struggle with the 'angel' (Gen 32:22-32), Tongue makes use of postmodern theories of textual production to argue that it is the 'paragesis', a parasitical form of writing between disciplines, that best foregrounds the complex performativity of biblical interpretation.